1993
DOI: 10.1111/j.1365-2796.1993.tb00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking induces insulin resistance—a potential link with the insulin resistance syndrome

Abstract: Smoking (also in habitual smokers) acutely impairs insulin action and leads to insulin resistance. Thus, smoking can be of importance for the development of the insulin resistance syndrome associated with risk for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
208
6
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(233 citation statements)
references
References 19 publications
13
208
6
6
Order By: Relevance
“…26 Norto Kawakami et al observed that the increase in NIDDM risk related to number of cigarettes smoked per day was modest when the number of cigarettes smoked per day was greater than 25. A similar pattern was observed by Attvall S et al 35 The authors suggested that smoking a certain number of cigarettes per day is sufficient for developing NIDDM and there is no further increase in risk beyond that amount. Similar "saturated" effects of number of cigarettes smoked per day have been reported from studies of smoking and serum lipoprotein disturbances and smoking and plasma fibrinogen levels.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…26 Norto Kawakami et al observed that the increase in NIDDM risk related to number of cigarettes smoked per day was modest when the number of cigarettes smoked per day was greater than 25. A similar pattern was observed by Attvall S et al 35 The authors suggested that smoking a certain number of cigarettes per day is sufficient for developing NIDDM and there is no further increase in risk beyond that amount. Similar "saturated" effects of number of cigarettes smoked per day have been reported from studies of smoking and serum lipoprotein disturbances and smoking and plasma fibrinogen levels.…”
Section: Discussionsupporting
confidence: 58%
“…34 In 1993 Attval et Al showed that smoking impaired insulin sensitivity and acutely impaired insulin action in otherwise healthy subjects. 35 In our study mean HbA1c values show an increasing trend with increasing age in both smokers (cases) and non-smokers (controls). While this can be attributed (even if, partially) to the effects of smoking in smokers (cases) the same cannot be said from the observed increase in non-smokers (controls).…”
Section: Discussionmentioning
confidence: 80%
“…Cigarette smoking is another potential confounder since it may cause acute insulin resistance (Attvall et al 1993;Frati et al 1996). Intake of dietary RS on the day before a meal challenge may improve glucose tolerance (Robertson et al 2002).…”
Section: Subject Preparationmentioning
confidence: 99%
“…It seems possible that the pronounced increase of ACTII and cortisol after smoking may in fact contribute to the distribution of body fat to visceral depots, particularly since women with an elevated WHR often smoke (12). Furthermore, recent studies have demonstrated that smokers often are insulin resistant (1,16). The elevation of cortisol and ACTH shown in this report and previously (2,(5)(6)(7)(8)15,17,20) might provide an explanation to these findings, because both these hormones are well known to be followed by insulin resistance.…”
Section: Discussionmentioning
confidence: 99%